Incentive Compensation When Executives Can Hedge the Market: Evidence of Relative Performance Evaluation in the Cross Section - Garvey, Gerald; Milbourn, Todd (Journal of Finance, 2003)
ABSTRACT Little evidence exists that firms index executive compensation to remove the influence of marketwide factors. We argue that executives can, in principle, replicate such indexation in their private portfolios. In support, we find that market risk has little effect on the use of stock‐based pay for the average executive. But executives' ability to “undo” excessive market risk can be hindered by wealth constraints and inalienability of human capital. We replicate the standard result that there is little relative performance evaluation (RPE) for the average executive, but find strong evidence of RPE for younger executives and executives with less financial wealth.